Tipologija modelov lingvogeneze slovanskih jezikov - Šekli, Matej (Slavistična revija, 2014)
The article discusses the typology of models of Slavic languages formation in geneto-linguistic sense. In the model of linguogenesis for each individual geolect, the author takes into account the type of its starting point and change as well as the manner of its formation.
Keywords: genealogical linguistic; geneolingvistika; geolect; geolekt; geolinguistics; geolingvistika; linguogenesis; lingvogeneza; Slavic languages; slovanski jeziki